ANALYSIS OF CHARACTER EDUCATION OF MAIN CHARACTERS IN THE NOVEL DEAR NATHAN BY ERISCA FEBRIANI - Putri Aliyanti; Putri Wulandari; Aldha Williyan (Educational Tracker, 2022)
This research is based on the fact that character education is important. Novels as a literary medium are good for teaching character education because they consist of a fairly long storyline and describe the development of characters in sufficient detail. This study aims to describe the character education of the main character in the novel Dear Nathan by Erica Febriani. This study uses a descriptive method and a descriptive approach. The data source in this research is the novel Dear Nathan. The data collection procedure was reading and note-taking techniques. The researchers used reading techniques by reading the novel Dear Nathan by Erisca Febriani repeatedly to identify which sentences were included in the value of character education. The results of this study can be concluded that the character education of the main character in the Dear Nathan novel by Erisca Febriani is honest, patient, responsible, willing to take risks, never give up, willing to sacrifice, critical, curious, friendly, cheerful, persistent, likes to help, independent, hardworking and friendly.